217 Assessment of Ultrasound Carcass Composition Equations to Predict Empty Body Gain. (12th April 2022) - Lancaster, Phillip A; Tedeschi, Luis O; Baker, Michael; Carstens, Gordon
Abstract: The objective of this study was to assess the accuracy of equations used to estimate ultrasound carcass composition for prediction of empty body gain (EBG). The dataset consisted of 8 trials with Angus and Brangus bulls or Brangus heifers (N = 897) fed moderate energy diets for 70 d. Initial and final ultrasound carcass measurements were obtained by trained technicians. Initial and final empty body fat percentage (EBF) was computed using 5 equations: 1) carcass trait equation from Guiroy et al. (2001; 10.2527/2001.7981983x), 2) carcass trait equation 1 from Tedeschi et al. (2004; 10.1016/S0308-521X(03)00070-2), 3) carcass trait equation 6 from Baker et al. (2006; 10.2527/jas.2006-006), 4) ultrasound trait equation 8 from Baker et al. (2006; 10.2527/jas.2006-006), and 5) pEBF = 27.1902 + 47.6268 × uBF – 0.5687 × uLMA – 0.1178 × uBF × pHCW + 0.0014 × uLMA × pHCW; R 2 = 0.64, RMSE = 2.46% developed from the training dataset of Baker et al. (2006). Empty body gain was predicted using NASEM (2016) equations. Eq. 5 had slightly improved R 2 (0.64 vs. 0.62) and RMSE (2.46 vs. 2.49%) compared with Eq. 4 in the training dataset. When comparing observed and predicted EBG, Eq. 4 had intercept and linear coefficients nearest to 0 and 1, respectively, the greatest CCC (0.799), and mean bias closest to 0 (0.025 kg/d) compared with the other equations. ADG, ultrasound traits, and sex were significant ( P < 0.05) variables accounting for variation in differences between observed and predicted EBG, suggesting that these equations are somewhat lacking in their ability to capture the relationships between ultrasound carcass composition traits and retained energy. ADG was less important and gain in LMA was more important in explaining differences between observed and predicted EBG for Eq. 5 than the other equations. These results indicate that use of live animal ultrasound measurements can predict retained energy with reasonably accuracy.